2004
DOI: 10.1007/s00467-004-1422-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of pediatric idiopathic urolithiasis?revisited

Abstract: The objective of the study was to update the evaluation and treatment of idiopathic urolithiasis in children in Western society. A secondary goal was to evaluate patients' compliance with high fluid intake. Over 2 years we prospectively studied children referred to us for idiopathic urolithiasis confirmed radiographically, excluding those with secondary disorders. A metabolic urinalysis, which included calcium, citrate, uric acid, oxalate, cystine, and creatinine, was ordered in all patients. Hypercalciuric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 17 publications
4
53
1
3
Order By: Relevance
“…These results are consistent with the recent findings by DeFoor et al (18) that urine calcium/citrate ratio in children is the best parameter to assess the risk for recurrent calcium stone formation. As often happens in clinical practice, not all stones were captured, hence no stone analysis was available in 14 of the 34 stone forming children (33). However, when the group of 20 children with known stone composition was compared with control children, the findings were the same as for the whole stone group (data not shown).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the recent findings by DeFoor et al (18) that urine calcium/citrate ratio in children is the best parameter to assess the risk for recurrent calcium stone formation. As often happens in clinical practice, not all stones were captured, hence no stone analysis was available in 14 of the 34 stone forming children (33). However, when the group of 20 children with known stone composition was compared with control children, the findings were the same as for the whole stone group (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…However, when the group of 20 children with known stone composition was compared with control children, the findings were the same as for the whole stone group (data not shown). Indeed, calcium stone has become the most common form of stone in developed countries (33,34). The likelihood of the remaining 14 hypercalciuric stone-forming children as not to have a calcium-based stone is low as we had included only children with hypercalciuria with radiologically documented stone and had excluded children with cystine, uric acid, and struvite stones, and those with hyperoxaluria or hypocitraturia, and children with history of UTI, or anatomic and functional abnormalities in the urinary and gastro intestinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that chloride sodium intake induces mild metabolic acidosis and may impair bone mass, as could be a risk factor for the formation of calculi [60] . On the other hand, the high potassium intake has an inverse effect on urinary calcium, i.e., reduces the excretion of urinary calcium [17,56] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in metaphylaxis of stones, water intake is the approach that has the optimal cost-beneit ratio [21]. However, it is not possible to monitor the luid intake of children in school, and children's compliance in hydration is poor in general [22]. Because the need for liquids varies with temperature and activity level, parents may be recommended to monitor hydration based on urine color and urine density, if possible.…”
Section: Fluid Intakementioning
confidence: 99%
“…Because the need for liquids varies with temperature and activity level, parents may be recommended to monitor hydration based on urine color and urine density, if possible. Urine densities that repeatedly measure higher than 1010 indicate inadequate luid intake [22].…”
Section: Fluid Intakementioning
confidence: 99%